Case reportSuccessful recanalization of total chronic occlusion of the superficial femoral artery by antegrade subintimal angioplasty with stenting using the Pioneer Plus Re-Entry Catheter - Szymański, Radosław; Wiernek, Szymon; Wiernek, Barbara; Konkolewska, Magda; Buszman, Paweł E.; Kiesz, Radosław S. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
The subintimal angioplasty is one of the most frequent techniques used for total chronic occlusion (CTO) treatment. Nevertheless, this approach is limited by the lack of controlled re-entry into the true lumen of the target vessel. We present a case of a 85-year-old man with symptomatic CTO of the left superficial femoral artery (SFA). After initially unsuccessful subintimal recanalization with Confianza wire, Pioneer Plus Catheter with Intravascular Ultrasound Volcano system guidance were used for a true lumen re-entry. Finally lesion was treated with angioplasty and stents. Procedure was successful without complications, no residual stenosis was noted. The patient was discharged home four hours after procedure. The one day and three weeks follow up showed no vascular complications and the patient had no residual symptoms. The ankle-brachial index of the left extremity has improved from baseline 0.22 to 0.98.